Review on Helicobacteriosis Associated Diseases - Almashhadany, Dhary Alewy; Mohammed, Hero Ismael; Aljoborey, Abdulmunem Dherar Abdullah (International Journal of Membrane Science and Technology, 2023)
Helicobacteriosis is a bacterial infection caused by Helicobacter pylori (H.pylori)(HP). which was discovered in 1982 by Australian scientists Barry Marshall and Robin Warren, who were later awarded the Nobel Prize in 2005.Epidemiological evidence has shown that H.pylori colonizes the upper gastrointestinal tract(GIT), and the infection is one of the most common human bacterial pathogens worldwide, with 4.4 billion infected individuals in 2015, but the prevalence varies according to situation and hygiene principles. Since this first isolation, it has become apparent that this organism may be one of the most common bacterial pathogens of humans, and it is one of the risk factors for adenocarcinoma. Thus, it was categorized as a group 1 carcinogen in 1994 by the World Health Organization (WHO). New infections with H.pylori are thought to occur as a consequence of direct human-to-human transmission, via either an oral-oral or fecal-oral route or both. H.pylori has been detected in stool, saliva, vomitus, and gastric refluxate, the material that has been subject to reflux, principally stomach acid that has leaked up into the esophagus. Clinically, H. pylori infection in humans is related to chronic gastritis, peptic ulceration, duodenal ulcer, and gastric cancer in addition to mucosa-associated lymphoid malignancies.According to the World Health Organization (WHO) estimates available at that time, it was supposed that about 4.4 billion infected individuals in 2015 were infected with H. pylori. These estimations can vary and are subject to change over time as recent investigations and information become obtainable. The prevalence of H. pylori is complex and affected by several factors, comprising age, clinical outcomes, geographical location, and socioeconomic status. A higher incidence was reported in unhygienic and economically poor areas; the rate of H. pylori infection in Africa, South America, and Asia was significantly higher than that in Western Europe, North America, and Australia. However, the disease spectrum of H. pylori infection shows a wide range of clinical aspects, including gastrointestinal diseases and extra gastric manifestations. In this review, we have described the general scope of these diseases.